(untitled) (Economics and region, 2024)
The article examines the problems of the formation of labor relations from the position of the employee and the employer in Ukraine during the war. Identified the growth of unemployment as the main factor in the change of the "employer’s market" to the "employer’s market". The formation of labor relations is the basis of the preservation of society, they must be implemented under current realities in accordance with the tasks of creating security of residence, management of employment and demography aimed at increasing the comfort of living of citizens due to the reconstruction, restoration and development of engineering and transport infrastructure, comprehensive assistance in solving social and humanitarian issues , maximum possible provision of decent living conditions and improvement of the population’s well-being. Further development in the perspective of world globalization processes in relation to labor relations also, according to the assessment of the International Labor Organization, also requires a special emphasis to eliminate physical and biological dangers arising as a result of increasing tensions in the worldThe main problem of employment is the reduction of production and the lack of a sufficient number of workers in labor professions. The changes in labor relations in accordance with the requirements of wartime, which provide for a higher level of labor intensity, have been evaluated. Labor relations in the conditions of war changed their specificity in accordance with the requirements of wartime, dictating a stricter use of workers to meet the needs of production. But, at the same time, on the part of the workers, the demand for the employer to ensure physical safety and working conditions, which make it possible to realize the basic needs of the worker and his relatives, comes first. On the part of the state, a difficult challenge is, on the one hand, the need to regulate labor relations to ensure compliance with the constitutional rights of citizens, and on the other hand, to allow a greater level of workload on employees to meet the needs of the economy in wartime conditions. The Ukrainian system of labor relations is undergoing significant upheavals related to the war, therefore preserving the country’s labor resources and creating conditions for their qualitative restoration is one of the current and promising tasks for the country’s development. The factor of ensuring the physical safety of labor is defined as a priority in ensuring the production process in the conditions of military operations. The role of state administration in regulating labor relations between the employee and the employer at the industrial and national levels in wartime is revealed.